5x-7y-2x² expand the following using stable indentity
Answers
Answered by
0
{2x} ^{2} - 5x - 7y = 0 \\
5x - 5y - 2y - {2x}^{2} = 0 \\ 5(x - y) - 2( x - y) = 0 \\ (x - y)(5 - 2) = 0 \\ x - y = 0 \: or \: 5 - 2 = 0 \\ x = y \: or \: 5 = 2[/tex]
I hope this help you
5x - 5y - 2y - {2x}^{2} = 0 \\ 5(x - y) - 2( x - y) = 0 \\ (x - y)(5 - 2) = 0 \\ x - y = 0 \: or \: 5 - 2 = 0 \\ x = y \: or \: 5 = 2[/tex]
I hope this help you
rohitkumargupta:
It is wrong
Similar questions
Biology,
7 months ago
Math,
1 year ago
Math,
1 year ago
History,
1 year ago
Social Sciences,
1 year ago